Undocumented saints: the politics of migrating devotions - Calvo-Quiros, William A. (Oxford scholarship online, 2022)
The book looks at five vernacular saints that have emerged in Mexico and have migrated into the US in the last one hundred years. Each chapter contextualises a particular vernacular saint within broader discourses about the construction of masculinity and the state, the long history of violence against women in the region, female erasure from history, the discrimination of non-normative sexualities, as well as US and Mexican investment in the control of religiosity within the discourses of immigration.